2020
DOI: 10.1098/rsos.200780
|View full text |Cite
|
Sign up to set email alerts
|

Early spread of COVID-19 in Romania: imported cases from Italy and human-to-human transmission networks

Abstract: We describe the early spread of the novel coronavirus (COVID-19) and the first human-to-human transmission networks, in Romania. We profiled the first 147 cases referring to sex, age, place of residence, probable country of infection, return day to Romania, COVID-19 confirmation date and the probable modes of COVID-19 transmissions. Also, we analysed human-to-human transmission networks and explored their structural features and time dynamics. In Romania, local cycles of transmission were preceded by imported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 30 publications
1
76
0
Order By: Relevance
“…With regard to the dynamic of the COVID-19 pandemic in Romania, it is important to note that more than five million Romanians are abroad and that, in March 2020, more than 250,000 Romanians returned in Romania [ 11 ]. Additionally, an important part of the Romanian diaspora is concentrated in the North of Italy [ 12 ]. Therefore, severe measures of social distancing during the State of Emergency (15 March–15 May 2020) were initially implemented that delayed the overburdening of the Romanian healthcare system that already had issues [ 5 , 6 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the dynamic of the COVID-19 pandemic in Romania, it is important to note that more than five million Romanians are abroad and that, in March 2020, more than 250,000 Romanians returned in Romania [ 11 ]. Additionally, an important part of the Romanian diaspora is concentrated in the North of Italy [ 12 ]. Therefore, severe measures of social distancing during the State of Emergency (15 March–15 May 2020) were initially implemented that delayed the overburdening of the Romanian healthcare system that already had issues [ 5 , 6 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Romania, the first case of SARS-CoV-2 infection was confirmed on 26 February 2020, a contact of an Italian citizen [ 13 ], and, 1 month later, on 22 March 2020, the first COVID-19 death was noted [ 14 ]. Among the first 147 COVID-19 cases in Romania, 88 were imported cases, with 64 from Italy [ 12 ]. At the first release of the present survey, there were around 9000 cases, more than 40,000 people quarantined at home, and more than 500 deaths from COVID-19 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pandemics are increasingly becoming a constant menace to the human race, with COVID-19 8 , 9 being the latest example. A second wave is creeping back in Europe and is poised to rage across the continent by fall 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Perc et al [105] proposed a method to determine the daily growth rates to reduce the risk of global spread of the COVID-19 pandemic. Similarly, Hancean et al [106] proposed human-to-human transmission networks and dispersion mechanism of the novel coronavirus. Ribeiro et al [107] shown the spread of novel coronavirus and they inspected the number of cases and deaths during the COVID-19 of the Brazilian cities' populations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hancean et al [106] proposed human-to-human transmission networks and dispersion mechanism of the novel coronavirus. Ribeiro et al [107] shown the spread of novel coronavirus and they inspected the number of cases and deaths during the COVID-19 of the Brazilian cities' populations. National and international association are essential for combating COVID-19 and other probable epidemics to be more organized for pandemics as early as possible [108].…”
Section: Introductionmentioning
confidence: 99%